SOFSEM 2013: theory and practice of computer science : 39th International Conference on Current Trends in Theory and Practice of Computer Science, Spindleruv Mlyn, Czech Republic, January 26-31, 2013. Proceedings - Groen, Frans C. A.; Italiano, Giuseppe F.; Nawrocki, Jerzy; Sack, Harald; Emde Boas, Peter (Lecture Notes in Computer Science, 2013)
This book constitutes the refereed proceedings of the 39th International Conference on Current Trends in Theory and Practice of Computer Science, SOFSEM 2013, held in Špindlerův Mlýn, Czech Republic, in January 2013. The 37 revised full papers presented in this volume were carefully reviewed and selected from 98 submissions. The book also contains 10 invited talks, 5 of which are in full-paper length. The contributions are organized in topical sections named: foundations of computer science; software and Web engineering; data, information, and knowledge engineering; and social computing and human factors.